Production, purification, and characterization of a beta-glucosidase of penicillium funiculosum NCL1 - Ramani, Gurusamy; Meera, Balasubramanian; Vanitha, Chinnathambi; Rao, Mala; Gunasekaran, Paramasamy (Applied Biochemistry and Biotechnology, 2012)
Penicillium funiculosum NCL1, a filamentous fungus, produced significantly higher levels of beta-glucosidase. The effect of initial pH, incubation temperature, and different carbon sources on extracellular beta-glucosidase production was studied in submerged fermentation. At 30 A degrees C with initial pH 5.0, enzyme production was increased by 48-fold upon induction with paper mill waste, as compared to commercial cellulose powder. In zymogram analysis, four isoforms of beta-glucosidases were observed with wheat bran whereas a minimum of one isoform was observed with other carbon sources. A major beta-glucosidase (Bgl3A) with the apparent molecular weight of similar to 120 kDa, induced by paper mill waste, was purified 19-fold to homogeneity, with a specific activity of 1,796 U/mg. Bgl3A was a monomeric glycoprotein with 29% of neutral carbohydrate content. It showed optimum activity at pH 4.0 and 5.0, optimum temperature at 60 A degrees C, and exhibited a half-life of 1 h at 60 A degrees C. K (m) of Bgl3A was found to be 0.057 mM with p-nitrophenyl beta-d-glucoside and V (max) was 1,920 U/mg. The purified enzyme exhibited glucose tolerance with a K (i) of 1.5 mM. Bgl3A readily hydrolyzed glucosides with beta-linkage. Bgl3A activity was enhanced (156%) by Zn2+ and was not affected by other metal cations and reagents. The supplementation of Bgl3A (5 U/mg) with Trichoderma reesei cellulase complex (5 FPU/mg) resulted in about 70% of enhanced glucose production, which emphasizes the industrial importance of Bgl3A.
Keywords: beta-Glucosidase; Paper mill waste; Penicillium funiculosum NCL1; Purification; Thermostability

In silico ligand binding studies of cyanogenic beta-glucosidase, dhurrinase-2 from Sorghum bicolor - Mahajan, Chavi; Patel, Krunal; Khan, Bashir Mohammad; Rawal, Shuban S. (Journal of Molecular Modeling, 2015)
Dhurrinase, a cyanogenic beta-glucosidase from Sorghum bicolor is the key enzyme responsible for the hydrolysis of dhurrin to produce toxic hydrogen cyanide, as a part of plant defence mechanism. Dhurrinase 1 (SbDhr1) and dhurrinase 2 (SbDhr2), two isozymes have been isolated and characterized from S. bicolor. However, there is no information in the literature about the three dimensional (3D) structure of SbDhr2 and molecular interactions involved between the protein and ligand. In this study, the three dimensional structure of SbDhr2 was built based on homology modeling by using the X-ray crystallographic structure of its close homologue SbDhr1 as the template. The generated 3D model was energy minimized and the quality was validated by Ramachndran plot, various bioinformatic tools and their relevant parameters. Stability, folding-unfolding and flexibility of the modeled SbDhr2 was evaluated on the basis of RMSD, radius of gyration (R-g) and RMSF values respectively, obtained through molecular dynamic (MD) simulation. Further, molecular docking was performed with its natural substrate dhurrin, one substrate analogue, three un-natural substrates, and one inhibitor. Analysis of molecular interactions in the SbDhr2-ligand complexes revealed the key amino acid residues responsible to stabilize the ligands within the binding pocket through non-bonded interactions and some of them were found to be conserved (Glu239, Tyr381, Trp426, Glu454, Trp511). Reasonably broader substrate specificity of SbDhr2 was explained through the wider entrance passage observed in comparison to SbDhr1.
Keywords: beta-Glucosidase; Dhurrinase; Molecular docking; Molecular dynamic simulation; Sorghum bicolor